MEDICAL AND SOCIAL STUDY OF UNCARED-FOR AND HOMELESS CHILDREN OF ST.-PETERSBURG - G.L. Mikirtichan; E.M. Cherkasova; A.Z. Likhtshangof ("Paediatrician" Publishers LLC, 2010)
The article presents the results of observation of uncared-for children in medical center during 10 years. Children and adolescents (n = 3,875, average age - 14,9 years old) were observed by pediatricians and doctors of particular specialities; an anonymous sociological survey was performed (n = 3,254). Doctors diagnosed infectious diseases (HIV, hepatitis B and C, syphilis) in 542 children and estimated the quality of life in 112 children. The study showed negative peculiarities of life and health mood of uncared-of children: deficiency of height and weight, nonobservance of personal hygiene, use of injection narcotics, polynarcotism. Sexual behavior of children is characterized by early debut of sexual contacts, low level of sexual competence, promiscuity, and inclusion into sex-business. There's a high prevalence of infections and parasitic diseases, including HIV-infection. The rates of quality of life are significantly decreased compared to the schoolchildren from successful families. Key words: uncared-for and homeless children and adolescents, life mood, prophylactic pediatrics, quality of life.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(1):5-11)